Adoption and diffusion of health information technology: The case of primary care clinics - Brant Callaway; Vivek Ghosal (Center for Economic Studies and ifo Institute (CESifo), 2012)
We empirically examine the determinants of adoption of information technology by primary healthcare clinics using a large sample of physician clinics from several States in the U.S. Ours is one of the first studies to intensively investigate primary care clinics. These clinics are important as they represent the frontlines in the delivery of services in this large and complex market. Our study generates several interesting results related to the adoption and diffusion of Health Information Technology (HIT), including: (1) the adoption probabilities vary considerably by the specific type of clinic; (2) in contrast to numerous studies in the broader technology adoption literature, we find little evidence to suggest a relationship between firm (clinic) size and the likelihood of adoption; (3) there appears to be no definitive relationship between the age of a clinic and the likelihood of adoption; (4) there is a strong effect of geographic location, as measured by specific types of urban and rural counties, on the likelihood of adoption; (5) market competitive forces appear to have a mixed influence on adoption; (6) there is a distinct State-specific effect suggesting that information privacy, medical malpractice laws and State initiatives may play an important role in adoption; and (7) HIT is diffusing at a faster rate over time. Our findings have the potential to provide a better understanding of the longer-run effectiveness and efficiency in the provision of healthcare, and crafting appropriate policy responses. We note some future extensions of our work.
Keywords: O33; I11; I18; M15; M21; 330; healthcare; primary care; health information technology; electronic medical records; technology; adoption; diffusion; urban and rural locations; competition; healthcare policy; Basisgesundheitsversorgung; E-Health; Informationstechnik; Innovationsdiffusion; USA